Adult Vaccination: The Current Scenario - Parth Pramod Godhiwala1 , Sunil Kumar2 , Sourya Acharya3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Vaccination is the process by which a person is made immune to various preventable diseases. Most of theemphasis is given to childhood vaccination and very little focus goes on towards immunizing the adults.Health care services in India has very less contribution to adult vaccination. Hence a desperate need hasemerged to develop strategies and schemes for adult vaccination. The disease burden in India is increasingfor both communicable and non-communicable diseases. By vaccinating adults against a disease that areknown to be life-threatening can reduce the mortality rates significantly. In a country like India with such ahuge population, vaccination can be a major intervention in preventing morbidity, mortality, and disabilitydue to many known and preventable diseases. There is no doubt that adult vaccination in India is negligibleas protecting adults by vaccination has never been considered as a preventive strategy. Hence there is a needto sensitize the health care providers in our country regarding the same. By vaccinating adults along withchildren, the chain of spreading the diseases can be broken and quality of life can be improved in a diseasefree world.